Beween Romanticism and Modernism - Dahlhaus, Carl 1928-1989 (Berkeley, CA University of California Press, 1980)
Carl Dahlhaus here treats Nietzsche's youthful analysis of the contradictions in Wagner's doctrine (and, more generally, in romantic musical aesthetics); the question of periodicization in romantic and neo-romantic music; the underlying kinship between Brahms's and Wagner's responses to the central musical problems of their time; and the true significance of musical nationalism. Included in this volume is Walter Kauffman's translation of the previously unpublished fragment, "On Music and Words," by the young Nietzsche.
Keywords: 19th Century (1801-1900); 20th Century (1901-2000); Music history